2018
DOI: 10.1186/s13018-018-0808-z
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of risedronate in reducing bone resorption after total hip arthroplasty: a meta-analysis of randomized control trials at a minimum of 6 months’ follow-up

Abstract: BackgroundRecently risedronate is suggested to be effective for the prevention and treatment of for osteoporosis in total hip arthroplasty. This meta-analysis aimes to evaluate the efficacy of risedronate in reducing femoral periprosthetic bone mineral density loss in patients undergoing primary total hip arthroplasty.MethodsA systematic search was performed in Medline (1966-31 October 2017), PubMed (1966-31 October 2017), Embase (1980-31 October 2017), ScienceDirect (1985-31 October 2017) and the Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Fourthly, we find that there are another four similar meta-analyses published online in 2018 [5][6][7][8]. All of them were performed following the guideline of PRISMA and four declared that they were the first meta-analysis on this topic, while none of them had a protocol registration in any platform, such as the Cochrane Library and PROSPERO.…”
Section: Dear Editorsmentioning
confidence: 90%
“…Fourthly, we find that there are another four similar meta-analyses published online in 2018 [5][6][7][8]. All of them were performed following the guideline of PRISMA and four declared that they were the first meta-analysis on this topic, while none of them had a protocol registration in any platform, such as the Cochrane Library and PROSPERO.…”
Section: Dear Editorsmentioning
confidence: 90%
“…[ 27 ] Meta-analysis 56,043 THA 331,660 TKA THA/TKA All bisphosphonates All-cause revision rate Prieto-Alhambra et al. [ 28 ] Case-control meta-analysis 10,524 THA/TKA All bisphosphonates All-cause revision rate Yang [ 29 ] Meta-analysis of RCTs 198 THA Risedronate Bone mineral density Teng [ 30 ] Meta-analysis 31,293 THA/TKA All bisphosphonates All-cause revision rate Zhou et al. [ 31 ] RCT 40 THA Zoledronic acid Bone mineral density Khatod et al.…”
Section: Benefits Of Bisphosphonates In Tjamentioning
confidence: 99%
“…found that patients who had osteoporosis and took zoledronic acid had an increase in BMD of 16% over 1 year after THA, compared with patients with osteopenia who lost 10% of their BMD in Gruen zone 1 over the same time period [ 34 ]. Similarly, Yang performed a meta-analysis of 198 THAs followed up for up to 6 months from the index surgery to evaluate the efficacy and safety of oral risedronate on BMD after THA [ 29 ]. These authors concluded that, in an uncemented femoral component, risedronate significantly reduces periprosthetic bone loss up to 6 months after THA, and no severe adverse events occurred.…”
Section: Benefits Of Bisphosphonates In Tjamentioning
confidence: 99%
See 1 more Smart Citation
“…Several quality studies (including systematic reviews and meta-analyses) have been performed in humans showing the early (up to 2 years) positive effect of the administration of mainly bisphosphonates on the preservation of periprosthetic bone stock, especially in cementless THAs at short to mid-term follow-up. [40][41][42][43][44][45][46][47][48] While pre-and postoperative bone mineral density measurements allow the prediction of mechanical bone quality, their relevance in predicting long-term failure in arthroplasty treatment remains unclear. 11,15 A retrospective cohort study revealed that bisphosphonates users had lower revision rates.…”
Section: The Effect Of Osteoporosis Medication On Bone-implant Interfacementioning
confidence: 99%